Developing organ dysfunction diagnostic criteria for children with cancer and post-hematopoietic cell transplantation: protocol of systematic review - Bashir, Michael; Islam, Sayeda; Wrigley, Jordan; Arias, Anita; Wösten-van Asperen, Roelie M.; Kertis, Kimberly K.; Hudson, Melissa M.; Rowan, Courtney M.; Talleur, Aimee C.; Wolf, Joshua; Oelkers, Benjamin; Hines, Melissa R.; et al. (Frontiers in Oncology, 2025)
BackgroundThe Pediatric Organ Dysfunction Information Update Mandate (PODIUM) proposed consensus criteria to define organ dysfunction in critically ill children. However, utilization of the PODIUM criteria in pediatric oncology patients and those who have received hematopoietic cell transplantation or cellular therapy (post-HCT/CAR) may inaccurately classify organ dysfunction in these patients due to differences in organ dysfunction etiology, pathophysiology, and risk factors for adverse outcomes. To address this gap, we report a study protocol to systematically review the performance of the PODIUM criteria for pediatric cancer and/or those treated with HCT and determine if adjustments are needed.ObjectiveThe objectives of this study will be to [1] identify evidence-based criteria for organ dysfunction predicting adverse outcomes among pediatric oncology and post-HCT patients, [2] use these findings to inform adapted consensus criteria (PODIUM-Onc) for organ dysfunction tailored to this high-risk population through a multidisciplinary modified Delphi process, and [3] describe knowledge gaps to guide future research.Data source and search strategyWe will perform a systematic literature review of studies published since January 1, 2004, using the following databases: MEDLINE (via PubMed), CINAHL (via EBSCO), EMBASE (via Elsevier), and Web of Science (via Clarivate). Search results will be filtered using a pediatric search hedge and further refined to children (0 to 21 years old) during or up to 1 year after treatment for cancer or HCT/CAR for malignancy. Publications without original data (e.g., comments, editorials, letters, notes, conference materials), studies with ≤ 10 patients, and those preceding January 1, 2004, will be excluded.Study selectionWe will include original studies in any language published since January 1, 2004, that meet all eligibility criteria and for which a full text is available.Data extractionData extraction will include information related to study characteristics, hospital characteristics, underlying population characteristics, patient population characteristics, and outcomes.Data synthesisWe will extract and report data on the study, hospital, and patient characteristics, outcomes, and risk of bias.ConclusionBy systematically reviewing and analyzing organ-specific factors associated with patient outcomes and synthesizing these findings through a modified Delphi consensus process, we aim to create consensus criteria that will be clinically relevant for pediatric oncology patients and HCT patients. These criteria will provide a foundation to guide clinical care and to support future research in this vulnerable patient population.